A Retrospective Chart Review of Dexamethasone Prescribing in Palliative Care Settings in Riyadh, Saudi Arabia - Fatimah Hussain Abu Qurain; Gassan Abudairi; Steven Callaghan; Muneerah Almutairi; Mahmoud Sroor; Ruth Evangelista; Faisal Al Kattan; Musab Aldhari (Saudi Journal of Medicine, 2026)
Background: Dexamethasone is crucial in palliative care for advanced cancer, improving symptoms like appetite loss and fatigue. However, guidelines are lacking, and side effects require close monitoring. The indications for corticosteroid use in this patient group are diverse, including the treatment of specific conditions such as spinal cord compression, elevated intracranial pressure, and loss of appetite. Due to the challenges in prescribing these medications for palliative care patients, there is evidence of suboptimal practices in the literature. This study aimed to examine the current patterns of corticosteroid prescribing in healthcare settings across Saudi Arabia and determine whether these practices align with international guidelines. Aim(s) of the Study: The objective of this study was to analyse current dexamethasone prescribing patterns in palliative care settings in Saudi Arabia and assess their alignment with international standards. Method: A retrospective chart review was conducted on inpatient palliative care patients who received dexamethasone at KFSHRC, Saudi Arabia, between January 1, 2022, and January 1, 2024. All available charts of patients under the care of the Palliative Care team who had a cancer diagnosis and received dexamethasone during that timeframe were included. Data collection focused on the number of patients prescribed dexamethasone, indications for use, choice of agent, dosages and adjustments, duration of treatment, occurrence of adverse effects, method of discontinuation, adherence to guidelines, and monitoring and review processes. Exclusion criteria: patients prescribed dexamethasone by other primary services will be excluded. Results: A total of 78 patients were included (median age 55.6 years), with the majority being female (56.4%) and having metastatic disease (89.7%). Gastrointestinal cancers were the most common diagnosis (33.3%), and 70.5% of patients were not receiving disease-modifying therapy at the time of dexamethasone initiation. The most frequent indications for dexamethasone were raised intracranial pressure/cerebral oedema (16.7%) and nausea/vomiting (15.4%), with a median daily dose of 4 mg; the IV route was most used (78.2%). Overall, 29.5% of patients demonstrated a documented clinical response, most commonly improvement in dyspnoea. Response was more frequent in patients treated for dyspnoea/airway obstruction (70.0%, p = 0.006) and in those receiving higher doses (p = 0.029). Adverse effects were rare (2.6%), limited to hyperglycemia. Median time to response was 2 days (IQR 2–3), with most responses occurring within 72 hours. Conclusion: This study showed that corticosteroids are widely prescribed in palliative care settings, both for specific and non-specific indications. These findings are generally consistent with international literature in this field, supporting the role of dexamethasone in targeted symptom palliation, especially in patients with respiratory compromise, while also highlighting the need for ongoing discussion about the role of corticosteroids in palliative care, as well as the need for clear documentation of indication and response in routine practice.